KEBUN RAYA BOTANI DENGAN SISTEM WTP (WATER TREATMENT PLAN) DI MAKASSAR - Wahid, Sri Innayah; Tauhid, Fahmyddin A'raaf (Nature: National Academic Journal of Architecture, 2025)
Tourism is one potential source of foreign exchange and have a larger share in building an economy that has a sale value into an object that is beneficial to the progress of Makassar. Tourist destinations that exist only in Makassar creates curiosity of visitors to visit. Visitors who come to invest accommodation all over the local tourism activities with local entrepreneurs. Domestic and foreign visitors are also a source of income for the people who live around the attraction. This report aims to restructure the physical elements areas such as land use, shape and mass of buildings, pedestrian paths, circulation and parking signage or markers, as well as support facilities into a regional botanical gardens botanical needed to achieve comfort for the users of land and WTP implement the system in the form of design which is sustainable (sustainable) and non architectural another goal to formulate natural plant engineering activities so that the botanical garden botany can be an alternative education center, grouping plants according to the climate and site conditions botanical garden botany, to determining system WTP work in botany botanical garden that can meet the needs of plants. The results of this report in the form of a botanical garden design botanical arrangement with WTP system (water Treatment Plan) in Makassar.